Norms and Ethics in Criminal Justice: Assessing Contemporary Legal Policy - L. Alfies Sihombing; Yeni Nuraeni (SEAN Institute, 2023)
This article explores the role of norms and ethics in shaping contemporary criminal law policy, with a particular focus on the challenges posed by the digital age and globalization. The research aims to understand how norms and ethics adapt and are applied in the face of cybercrime and rapid socio-political change. It also examines the impact of different approaches to the integration of norms and ethics across different criminal law systems in the world, and how these differences affect the effectiveness of justice enforcement at the international level. Through an analytical and evaluative approach, this article provides an in-depth analysis of the complex interactions between norms, ethics and criminal law, and the implications for the future of criminal justice. Taking into account social dynamics, technological advancements, and human rights protection needs, this research highlights the importance of continuous adaptation in criminal law policy in order to remain relevant and effective. The article also emphasizes the importance of constructive dialogue, cross-cultural understanding, and joint efforts in harmonizing differences in norms and ethics to effectively address global crime.